ANALISIS YURIDIS KEDUDUKAN HUKUM LEMBAGA PEMBERI FATWA HALAL DI BEBERAPA NEGARA - Aditya, Zaka Firma; Al-Fatih, Sholahuddin (Wacana Hukum, 2019)
AbstractConsuming halal and safe food products is a constitutional right of citizens. This right is realized through guarantee of halal products, the institution authorized to issue fatwa halla on a product is LPPOM MUI. The results showed that LPPOM MUI issued a halal certificate for a product after previously going through a trial process at the MUI Fatwa Commission. Although judicially the position of MUI is not a state institution, the presence of the MUI, especially LPPOM MUI, can answer the needs of the community. Halal certificates from LPPOM MUI can at least provide legal certainty for the community. Abroad, halal certification institutions are government or private institutions that have their own statutory regulations and standards.AbstrakMengkonsumsi produk pangan halal dan aman merupakan hak konstitusional warga negara. Hak tersebut diwujudkan melalui jaminan produk halal, lembaga yang berwenang mengeluarkan fatwa halla atas suau produk adalah LPPOM MUI. Hasil penelitian menunjukkan bahwa LPPOM MUI mengeluarkan sertifikat halal atas suatu produk setelah sebelumnya melalui proses sidang di Komisi Fatwa MUI. Meskipun secara yuridis kedudukan MUI bukan merupakan lembaga negara, namun kehadiran MUI, terutama LPPOM MUI, bisa menjawab kebutuhan masyarakat. Sertifikat halal dari LPPOM MUI setidakya bisa memberikan kepastian hukum bagi masyarakat. Di luar negeri, lembaga sertifikasi halal merupakan lembaga pemerintah atau swasta yang memiliki perundang-undangan dan standar resmi tersendiri.